UP CMC in focus : a descriptive study on the communication patterns of the UP-CMC faculty and staff - Garra, Ernestine O.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This study aims to describe the communication patterns of the faculty and staff of the University of the Philippines College of Mass Communication (UP-CMC). The researcher felt the need for a more updated study on the CMC since the last one was undertaken eleven (11) years ago. This research follows a descriptive approach and uses in-depth interviews, interview schedules, focus group discussion, document analysis and observation as methods in obtaining data. Respondents for the in-depth interviews are the CMC-Dean, three (3) department chairs, the Administrative Officer and the Head Librarian. Ten (10) faculty members and ten (10) administrative staff from the different departments answered the interview schedules. Four (4) library staff participated in the focus group discussion. Types of information received by the faculty and staff can be classified according to source. There are those that come from outside the university, information from the U.P. System and the U.P. Diliman levels, and those information within the College. All information coming to the College are largely in written forms such as memoranda and others. In the CMC, channels of communication are more varied and the dissemination of information is faster. Interdepartmental and intradepartmental communications were found to be largely informal. The communication patterns in the CMC follow the flow in its organizational structure wherein those with "line" functions such as the department chairs and the administrative officer have direct interaction with the Dean. Those with support functions such as the administrative staff have lesser interaction since they are not directly under his supervision. It was likewise found out that apparently some staff do not have a clear understanding of the roles and functions of his/her co-workers and superiors. With this, the researcher recommends for them to have series of workshops and training where their and their superiors' functions are explained. Likewise, the library staff need to have more interaction with their head. The feeling of alienation they have vis-a-vis the whole CMC is due to less interaction with the administration, the faculty and other staff. A thorough research using quantitative and qualitative methods is recommended for it to be used by those in the supervisory positions in reviewing the status of CMC as an organization.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Communication and traffic -- Philippines -- Employees; UP-CMC faculty and staff, Communication and traffic -- Philippines